1992
DOI: 10.1002/hep.1840160422
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Topical Methyl Tert–Butyl Ether or Ethyl Propionate on Gallbladder Histology in Animals: A Comparison of Two Solvents for Contact Dissolution of Cholesterol Gallstones

Abstract: Experiments were performed in anesthetized rabbits and piglets to assess gallbladder mucosal injury during irrigation with methyl tert-butyl ether, a C5 ether, or ethyl propionate, a C5 ester--two organic solvents used in the contact dissolution of cholesterol gallstones. In 44 New Zealand White rabbits, the gallbladder was exposed to individual solvents or saline solution through a transhepatic catheter for 2 hr. Gallbladders were then harvested and fixed immediately or after a recovery period of 1, 4 or 8 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Studies in pigs conducted by Oliver Esch in our laboratory indicated that the gallbladder epithelium was completely destroyed by MTBE, but quickly regenerated. 112 In our laboratory in San Diego, Salam Zakko, a fellow with remarkable talents in electronics, developed a highly intelligent pump capable of inducing turbulent flow around the gallstone; a pressure sensor that fed back on the inflow and outflow pumps kept the solvent in the gallbladder even if there was gallbladder contraction. 113,114 We found that ethyl propionate (a C 5 ester) dissolved gallstones in vitro as rapidly as MTBE (a C 5 ether), and was much better tolerated by the patient because of its lower volatility and rapid metabolism.…”
Section: Contact Dissolution Of Cholesterol Gallstonesmentioning
confidence: 99%
“…Studies in pigs conducted by Oliver Esch in our laboratory indicated that the gallbladder epithelium was completely destroyed by MTBE, but quickly regenerated. 112 In our laboratory in San Diego, Salam Zakko, a fellow with remarkable talents in electronics, developed a highly intelligent pump capable of inducing turbulent flow around the gallstone; a pressure sensor that fed back on the inflow and outflow pumps kept the solvent in the gallbladder even if there was gallbladder contraction. 113,114 We found that ethyl propionate (a C 5 ester) dissolved gallstones in vitro as rapidly as MTBE (a C 5 ether), and was much better tolerated by the patient because of its lower volatility and rapid metabolism.…”
Section: Contact Dissolution Of Cholesterol Gallstonesmentioning
confidence: 99%
“…The procedure required some hours for complete dissolution, and as described, it required professional personnel to perform the infusion and aspiration . In studies performed in pigs, the gallbladder epithelium was observed to be destroyed by either solvent, although it recovered rapidly ( 443 ). There There is still much is to be learned about the effect of individual bile acids on the microbiome ( 465 ).…”
Section: Topical Dissolution With Organic Solventsmentioning
confidence: 99%
“…47,50,51 The industrial chemical intermediate, dibutyltin dichloride, has been used as a model for the induction of acute pancreatitis in laboratory rodents, but which also induces a primary biliary mucosal necrosis of the common bile duct and larger interlobular ducts of the liver. [52][53][54][55] The necrosis of the epithelial cells is followed by a series of secondary pathological changes such as submucosal edema, extrahepatic cholestasis, and inflammation both within the affected tissues and throughout the periportal regions of the liver lobules. Serum bilirubin, ALP, GGT, and ALT are frequently elevated due to the secondary effects on the liver 56 but are not pathognomonic of primary biliary toxicity.…”
Section: Biliary Mucosal Necrosismentioning
confidence: 99%